Minorities, Muslims and Shari'a: some reflections on Islamic law and Muslims without political power - Hellyer, H. A. (Islam and Christian-Muslim relations, 2007)
Muslims are defined as Muslims by their sacred law; as such, they constitute a religious community delineated, theoretically and practically, according to a notion of jurisprudence. The comprehensive nature of that law has led many to doubt the ability of Muslims to integrate into non-Muslim societies, and the confusion remains in various ways in the present day, with many continuing to question it. Both Muslims and non-Muslims appear to be aware that for a large number of Muslims in the EU sacred law is not only useful but imperative for understanding their current situation. Looking at how jurists and intellectuals understood the role of Shari in both the past and the present is therefore of great interest to scholars and students in the field of Islamic studies in Europe.